Effect of telephonic nurse follow-up on maternal self-efficacy, breastfeeding, and immunization among late preterm infants in selected tertiary government hospitals - Jose, Anne Margareth V. (Manila: College of Nursing, University of the Philippines Manila, 2023)
After hospital discharge, mothers face unmet needs for practical health information and emotional support in caring for late preterm infants, which can lead to untoward health consequences. Existing local strategies are only partially operative, and new solutions are needed. The effectiveness of adapting an intervention based on telehealth, which was suggested to yield positive health outcomes, has yet to be discovered. -- Using a pretest-posttest control group design, this study aims to determine the effectivity of telephonic nurse follow-up (TNF) on maternal self-efficacy (MSE) in caring for the late preterm, breastfeeding, and adherence to infant immunization. -- The participants were mothers with late preterm infants (LPI) who have been discharged from the NICUs or special care nurseries of selected tertiary government hospitals in Metro Manila, Philippines. They were randomized into either the experimental or control group. The experimental group (n= 25) received TNF. This intervention comprises seven follow-up phone calls from nurses trained to deliver the intervention spanning six weeks from the infant’s discharge. The control group (n= 27) did not receive the intervention but was to contact the research hotline if health concerns arose. Data were gathered 24 hours after discharge and after eight weeks through telephone-based questionnaires administered by the data collector blinded to group conditions. -- Key finds indicate a significant increase in the experimental group’s breastfeeding knowledge, 8.19 (SD=1.08) vs. 8.90 (SD= 0.94), p= .035, and a decline in the control group’s exclusive breastfeeding practice (p=.039) contrary to that of the experimental group, from baseline to after eight weeks. However, no significant difference was found between the groups’ breastfeeding outcomes after eight weeks due to the small sample and incomplete data sets. Changes in the experimental group outcomes also cannot be entirely attributed to the intervention since it had more multiparous mothers with prior breastfeeding experience. Other factors, such as predisposition to lower MSE, infant sickness, and shared reasons behind immunization delays, influenced the outcomes and are not directly addressed by the educational support intervention. Although it had no effect on MSE and adherence to infant immunization, mothers were highly satisfied with its accessibility during crucial times in LPI care, the educational value, emotional comfort, and mental health support it provided them as postpartum mothers during the height of the COVID-19 pandemic. -- Telephonic nurse follow-up is a helpful strategy appreciated by postpartum mothers with LPIs during the COVID-19 pandemic. However, further research with a bigger sample size and more power is needed to detect its effect on breastfeeding outcomes.
Thesis (Master of Arts in Nursing - Maternal and Child Nursing) -- University of the Philippines Manila, August 2023.
Keywords: Telecommunication in medicine -- Premature infants; Telephonic nurse